The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/clen.202100280
|View full text |Cite
|
Sign up to set email alerts
|

Drop Size Distribution and Effective Determination of the Constitution of Throughfall Droplets under Maize Canopy

Abstract: Sprinkler irrigation has dominated the irrigation erosion, and droplet diameter is an important determinant. To clarify the influence of maize canopy and sprinkler droplets landing angle on drop size distribution, distribution trend, and throughfall droplets diameters, the information on droplet size and velocity are collected via 2D‐video‐disdrometer. The results showed that due to the presence of maize canopy and the decrease in landing angle, the proportion of the tiny droplets (<2 mm) within throughfall in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…As shown in supplemental materials, this study placed the needle vertically to achieve the scattering of sprinkler droplets, and the sprinkler water could be sprayed upward. The vertical falling of sprinkler water droplets could avoid the effect of landing angle on the ability of crop canopy to funnel sprinkler water because our previous work showed that the chance of their contact with corn canopy would be greater with the smaller landing angle (Zhu et al, 2021(Zhu et al, , 2022. In addition, three-needle diameters (0.70, 2.00, and 2.80 mm) were tested to regulate droplet diameter.…”
Section: Sprinkler Irrigation Water Dropletsmentioning
confidence: 99%
“…As shown in supplemental materials, this study placed the needle vertically to achieve the scattering of sprinkler droplets, and the sprinkler water could be sprayed upward. The vertical falling of sprinkler water droplets could avoid the effect of landing angle on the ability of crop canopy to funnel sprinkler water because our previous work showed that the chance of their contact with corn canopy would be greater with the smaller landing angle (Zhu et al, 2021(Zhu et al, , 2022. In addition, three-needle diameters (0.70, 2.00, and 2.80 mm) were tested to regulate droplet diameter.…”
Section: Sprinkler Irrigation Water Dropletsmentioning
confidence: 99%